Alterações morfológicas na placenta e no ovário de preás (Galea spixii Wagller, 1832) aos 30 dias de gestação submetidos a diferentes condições de iluminação - Bezerra, Ferdinando Vinícius Fernandes (2018)
The spix’s yellow toothed cavy has the body covered by soft hairs, colors ranging from gray to brown and are devoid of tail. The thoracic limbs present four digits and the pelvic limbs only three, and are short. Similarities of the reproductive characteristics of spix’s yellow-toothed cavy with superior primates make them potential experimental models, among them, the gestational period, the size of the offspring, the development of the pups, the placentation and the subplacenta. In general the reproductive cycle is influenced by hormonal mechanisms, among them the one regulated by melatonin seems to act on the preá, since this species is considered like animal of twilight habit. Thus, observing the characteristics of the species, the objective was to study the placenta, subplacenta and ovary of preá at 30 days of gestation submitted to different lighting conditions. For this it was used 15 female pretas with copula monitored vaginal cytology. Once the females were identified, the females were separated into groups, one being subjected to constant lighting, called a light group, another being submitted to a constant dark called a dark group, and the third group maintained under normal conditions. The placentas and ovaries were collected at the thirty-day gestation, which were weighed and measured. The samples were fragmented fixed for 48 h in 4% paraformaldehyde in 0.1 M PBS and pH 7.4, and embedded in paraffin according to usual techniques. Sections of five micrometers were serially collected and stained by HE. Based on the Cavalieri principle, the reference volume was calculated and, with the aid of ImageJ® (bundled with 64-bit Java 1.6.0_24) point-and-line test systems, the volume density, surface density and the surface area for the placenta and to calculate the follicular population of the ovaries of each experimental group. The data were statistically analyzed using SigmaPlot (Systat Software Inc) program with significance level p≤0.05. immunofluorescence was also performed for melatonin receptors (Santa Cruz Biotechnology, Inc.). The spix’s yellow-toothed cavy placenta presented significant morphometric differences between the control group and the others in all aspects analyzed. The largest volume was observed in the control group (5.37 cm3) and the lowest in the clear group (3.40 cm3) and among the placental constituents the ones connected to the interlobe were more influenced by the absence of light, the subplacenta presented difference in stage of development between groups, a condition evidenced by the difference in volume. The vascular area showed increase in the light and dark groups in relation to the control group, as well as the distribution of the receptors in the placental tissue. The ovaries had an ellipsoid shape, a smooth surface, a yellow color. The most abundant follicles were the primordial in all groups with no significant difference. However, the antral follicles showed significantly higher numbers in the dark group when compared to the other groups and the marking for melatonin receptors was more evident in mature follicles and especially in the dark group. Thus, it is concluded that the different lighting conditions cause morphological changes in the placental and ovarian tissue of preas and especially the absence of light, influence the morphology of the ovary